Neoteric Solvents for Rare Earths Processing: Perspectives on the Potential of Ionic Liquids and Deep Eutectic Solvents from a Bibliometric Analysis - Romero-Figueroa, J; Quijada-Maldonado, E; Abejon-Elias, R (Taylor and Francis Ltd., 2024)
Rare earth elements have become critical elements in today’s technological societies and neoteric solvents, such as ionic liquids (ILs) and deep eutectic solvents (DESs), are being called upon to replace traditional organic solvents in order to improve the environmental sustainability of rare earth processing. A bibliometric analysis was performed to investigate the scientific documents published in the Scopus database until 2023 regarding the use of ILs and DESs for rare earths processing. The search identified 731 papers since the pioneering works in the last years of the 20th century and the amount of accumulated published documents throughout time followed a quadratic evolution. China, the main producer of rare earths worldwide, was the most prolific country, publishing 276 documents (37.8% contribution), almost four times higher than the contribution of the United States (75 documents), the second country in the ranking. The triad of important keywords consists of ionic liquids, rare earths and extraction. In addition to separation by solvent extraction, leaching of rare earths from mineral ores and secondary resources such as e-waste using ILs and DESs has been extensively investigated. In addition, these innovative solvents can be considered as promising media for electrowinning processes to obtain pure rare earths. © 2024 Taylor & Francis Group, LLC.
Keywords: Rare earths; ionic liquids; deep eutectic solvents; processing; extraction; leaching; recovery; bibliometric analysis; research trends